The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.31234/osf.io/q6zfh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Meta-Analysis of Conditioned Fear Generalization in Anxiety-Related Disorders

Abstract: Objective: Generalization of conditioned fear is adaptive in some situations but maladaptive when fear excessively generalizes to innocuous stimuli with incidental resemblance to a genuine threat cue. Recently, empirical interest in fear generalization as a transdiagnostic explanatory mechanism underlying anxiety-related disorders has accelerated. As there are now several studies of fear generalization across multiple types of anxiety-related disorders, the authors conducted a meta-analysis of studies reportin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In addition to such intergroup biases, dysfunctional social threat learning may contribute to the development and maintenance of psychopathological fear and anxiety. The influence of anxiety on threat generalization (Cooper et al, 2022;Dunsmoor & Paz, 2015) may be particularly relevant for understanding dysfunctional intergroup processes. Another interesting followup question concerns the reciprocity of outgroup categorization and threat generalization in intercultural settings with different visual groups (Vizioli et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to such intergroup biases, dysfunctional social threat learning may contribute to the development and maintenance of psychopathological fear and anxiety. The influence of anxiety on threat generalization (Cooper et al, 2022;Dunsmoor & Paz, 2015) may be particularly relevant for understanding dysfunctional intergroup processes. Another interesting followup question concerns the reciprocity of outgroup categorization and threat generalization in intercultural settings with different visual groups (Vizioli et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CRs are not limited to the CSs but can spread also to stimuli resembling it (Generalization Stimuli or GSs; e.g., a circle that is a bit smaller than the CS+). This shows that CRs can be elicited not only by stimuli that are directly associated with the original aversive event, but also by stimuli that share formal or perceptual similarities with the CS (Cooper et al, 2022;Dymond et al, 2015;Fraunfelter et al, 2022;Honig & Urcuioli, 1981). Importantly, fear generalization may be a mechanism for why fear responses can generalize to neutral stimuli or situations even in the absence of direct conditioning.…”
Section: Fear Generalization In Individuals With Subclinical Levels O...mentioning
confidence: 90%
“…The typical way for investigating the acquisition and maintenance of panic symptomatology in humans is differential fear conditioning procedures (Cooper et al, 2022).…”
Section: Fear Generalization In Individuals With Subclinical Levels O...mentioning
confidence: 99%
“…Another construct that has recently gained attention is overgeneralization, that is the tendency to respond to stimuli somewhat similar to those that predict an aversive event. It has been observed that healthy participants who score high on anxiety (Sep et al, 2019) and participants with a clinical diagnosis (Cooper et al, 2022) both show more generalization than either people scoring low on anxiety or without a clinical diagnosis. Similarly, it has been observed that in individuals with anxiety, the CS+/CS-discrimination proceeds slower (CS refers to a conditioned stimulus and +/-refer to the Growth of anxiety 4…”
mentioning
confidence: 99%